Utilization of Supply Chain Management for BUMD - Arifin, Zainal (Adpebi Science Series, 2022)
In achieving the state's goal of providing comprehensive welfare for all Indonesian people, BUMDes has an equal distribution role and grants village autonomy so that it does not depend on the state. BUMDes which in its implementation has problems such as the utilization of existing resources and the effectiveness of production in the business activities carried out is something that must receive attention because this is a common problem but will pose a big obstacle if not handled properly. For this reason, Supply Chain Management may provide a benefit which can solve problems that occur in BUMDes business activities. Therefore, this study aims to explore and find answers to the Utilization of Supply Chain Management for BUMDes. Researchers in this study used a qualitative method which used books and journals that might be available to researchers as the main source and other relevant data as secondary sources. The researcher found that the use of Supply Chain Management in BUMDes business activities has a positive and significant effect if done correctly, because by using this method, BUMDes can make better use of their human resources and the provision of production goods will be wider, not only for local people. the surrounding area can even reach the international market if done properly.